2003
DOI: 10.1021/ja021484x
|View full text |Cite
|
Sign up to set email alerts
|

An Ionic Liquid-Supported Ruthenium Carbene Complex: A Robust and Recyclable Catalyst for Ring-Closing Olefin Metathesis in Ionic Liquids

Abstract: The synthesis of an ionic liquid-supported olefin metathesis catalyst derived from Grubb's ruthenium carbene complex is described. This new supported catalyst has been used in BMI.PF6 solvent, and this allowed success in solving the challenging problem of catalyst recycling. The IL catalyst in BMI.PF6 can be recovered and reused up to 10 consecutive cycles in RCM reactions of several dienes with excellent conversions. Moreover, the IL catalyst shows a remarkable stability in BMI.PF6 and can be stored several m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(120 citation statements)
references
References 14 publications
1
118
0
1
Order By: Relevance
“…The 29 Si solid state NMR data, some textural properties and the ligand loading of hybrid materials 8 are summarized in Table 1. 29 Si CP-MAS NMR of 8b-e confirmed the covalent bonding of the organic moiety to the matrix by the appearance of T 2 and T 3 signals due to the ligand in addition of the characteristic Q 3 and Q 4 signals due to the condensed TEOS. The 29 Si CP-MAS spectrum of 8dSi showed a signal around 11.9 ppm corresponding to the À SiMe 3 unit and the intensity of the Q 3 absorption (À103.1) decreased considerably ( Figure 2).…”
Section: Preparation Of Hybrid Materials and Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 29 Si solid state NMR data, some textural properties and the ligand loading of hybrid materials 8 are summarized in Table 1. 29 Si CP-MAS NMR of 8b-e confirmed the covalent bonding of the organic moiety to the matrix by the appearance of T 2 and T 3 signals due to the ligand in addition of the characteristic Q 3 and Q 4 signals due to the condensed TEOS. The 29 Si CP-MAS spectrum of 8dSi showed a signal around 11.9 ppm corresponding to the À SiMe 3 unit and the intensity of the Q 3 absorption (À103.1) decreased considerably ( Figure 2).…”
Section: Preparation Of Hybrid Materials and Catalystsmentioning
confidence: 99%
“…The mixture was filtered under nitrogen atmosphere with a cannula and the solid was washed 4 times with 4 mL portions of anhydrous dichloromethane. The combined filtrates were evaporated to yield 14 [29] Adv. Synth.…”
Section: Preparation Of Hybrid Catalyst 10fmentioning
confidence: 99%
“…However, attachment of an "ionic liquid tag" to catalyst ligands hugely improves the recyclability of the system. [12][13][14][15] Interestingly, neither of these nor most other studies involving transition metal catalysts attach any importance to the purity of the ionic liquid used as solvent, although it is known that impurities such as water, amines or halides, stemming from the preparation of the ionic liquid, affect the reaction outcome, especially if transition metal catalysts are used. [4,[18][19][20][21][22][23][24][25][26][27][28][29][30][31] In this sense, the conclusions drawn from this present study are certainly transferable to other catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…With an increase of the scan rate, the oxidation peak potential shifted more positively and the reduction potential shifted more negatively, while the peak currents increased linearly with an increase of the square of the scan rate (inset A). This revealed that the electrochemical behavior of the complex chemsorbed on the surface of the ligands showing a diffusion-confined redox process [20].…”
Section: H Nmr Analysismentioning
confidence: 95%